The Effect Of Liquidity, Leverage, And Company Size On Tax Aggressiveness In Industrial Sector Companies On The Indonesia Stock Exchange For The 2019-2021 - MANURUNG, Rineke Ester Dian; PANGERAPAN, Sonny; MINTALANGI, Syermi (PT Keberlanjutan Strategis Indonesia, 2022)
Taxes have a very important role in economic growth in Indonesia which is reflected in the state budget that tax contributions dominate compared to non-tax revenues. Tax revenues must be optimally increased so that economic growth runs well. In the operational activities of the company, taxes are recognized as a burden on the company, so it does not rule out the possibility that the company carries out tax aggressiveness actions by minimizing the tax burden that must be paid. This study aims to examine the effect of liquidity, leverage, and company size on tax aggressiveness in industrial sector companies on the Indonesia Stock Exchange for the 2019-2021. In this study using secondary data. The population in this study is the industrial sector companies listed on the Indonesia Stock Exchange with a population of 55 companies and the type of sampling in this study uses purposive sampling. This type of research is quantitative research. The method of analysis in this study is descriptive statistics, classical assumption test, multiple linear regression, and hypothesis testing. The results showed that liquidity partially has no effect on tax aggressiveness, leverage has an effect on tax aggressiveness, and firm size has a negative effect on tax aggressiveness.